The Consolidated Medium-Term Income and Expenditure Framework. (Policy Papers; Policy Paper ;, 2012)
This paper updates the consolidated income and expenditure outlook and the projected accumulation of precautionary balances over the medium-term. The paper incorporates and extends the income and budget projections in the companion papers; these projections are also in line with those discussed in the recent paper on the review of precautionary balances.